2021
DOI: 10.1007/s43630-021-00057-3
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic inactivation of planktonic Staphylococcus aureus by sodium magnesium chlorophyllin and its effect on the storage quality of lettuce

Abstract: Photodynamic inactivation (PDI) is a fast and effective non-heat sterilization technology. This study established an efficient blue light-emitting diode (LED) PDI with the photosensitizer sodium magnesium chlorophyllin (SMC) to eradicate Staphylococcus aureus in food. The antibacterial mechanisms were determined by evaluating DNA integrity, protein changes, morphological alteration, and the potency of PDI to eradicate S. aureus on lettuce was evaluated. Results showed that planktonic S. aureus could not be cle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…These watersoluble derivatives exhibit an improved photosensitivity and are proven to be safe in the food industry. Under the irradiation of 455-460 nm LED, the sodium magnesium chlorophyllin (5.0 μmol/L) efficiently inactivated ∼8 Log CFU/mL of S. aureus at a dose of 1.14 J/cm 2 within 10 min at 25 • C. Meanwhile, the cell membrane, protein, and DNA were the vulnerable attacking targets for the sodium magnesium chlorophyllin-mediated PDI (Yan et al, 2021). Josewin et al (2018b) established the sodium chlorophyllin-mediated PDI using 405 and 460 nm LEDs, and found that the PDI inactivated the cocktail of L. monocytogenes and Salmonella on cantaloupe rinds at a dose of 1210 J/cm 2 for 405 nm LED and 5356 J/cm 2 for 460 nm LED.…”
Section: Exogenous Chlorophyllin-mediated Pdimentioning
confidence: 99%
See 2 more Smart Citations
“…These watersoluble derivatives exhibit an improved photosensitivity and are proven to be safe in the food industry. Under the irradiation of 455-460 nm LED, the sodium magnesium chlorophyllin (5.0 μmol/L) efficiently inactivated ∼8 Log CFU/mL of S. aureus at a dose of 1.14 J/cm 2 within 10 min at 25 • C. Meanwhile, the cell membrane, protein, and DNA were the vulnerable attacking targets for the sodium magnesium chlorophyllin-mediated PDI (Yan et al, 2021). Josewin et al (2018b) established the sodium chlorophyllin-mediated PDI using 405 and 460 nm LEDs, and found that the PDI inactivated the cocktail of L. monocytogenes and Salmonella on cantaloupe rinds at a dose of 1210 J/cm 2 for 405 nm LED and 5356 J/cm 2 for 460 nm LED.…”
Section: Exogenous Chlorophyllin-mediated Pdimentioning
confidence: 99%
“…Under the irradiation of 455–460 nm LED, the sodium magnesium chlorophyllin (5.0 μmol/L) efficiently inactivated ∼8 Log CFU/mL of S. aureus at a dose of 1.14 J/cm 2 within 10 min at 25°C. Meanwhile, the cell membrane, protein, and DNA were the vulnerable attacking targets for the sodium magnesium chlorophyllin‐mediated PDI (Yan et al., 2021). Josewin et al.…”
Section: Inactivation Potency Of Pdi Against Planktonic Bacteriamentioning
confidence: 99%
See 1 more Smart Citation
“…Most recently, photo-illuminated (at 450 nm - blue light) RF was shown to have biofilm-disrupting activity against both mono and mix S. aureus and E. coli biofilms [ 38 ]. Chl-mediated API was reported to be effective against S. aureus for food preservation and decontamination [ [ 39 , 40 ]]. Several other studies have also indicated an effective inactivation of planktonic S. aureus cells by photosensitized chlorophyllin copper sodium salt [ 41 ], or chlorophyllin sodium magnesium salt, which has a superior antimicrobial activity to the former under irradiation of blue light [ 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…[ 15 , 16 , 17 ]. In addition, chlorophyll and its derivatives (especially water-soluble chlorophyllin) exhibit pronounced photodynamic properties against bacteria [ 9 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%